An exploratory investigation into Tshwane Postmodern consumers' consciousness and practices that relate to sustainable food procurement - Marx-Pienaar, Nadene J.M.M. (University of Pretoria, 2015)
Dissertation (MA)--University of Pretoria, 2014.